Reinforcer Choice on Skill Acquisition for Children with Autism Spectrum Disorder: a Systematic Replication - Northgrave, Jessie (Behav Anal Pract, 2018)
Providing students with autism spectrum disorder (ASD) a choice of putative reinforcers during learning trials may confer advantage during skill acquisition programming. However, such advantage should not be assumed and may not be associated with the most efficient instructional arrangement. In the current study, we taught labels of common object or conditional discriminations to participants with ASD and evaluated efficiency of instruction across child- and experimenter-choice instructional conditions. The results indicated that the most efficient acquisition was observed during the experimenter-choice condition for both participants.